2006
DOI: 10.1194/jlr.m500362-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

One generation of n-3 polyunsaturated fatty acid deprivation increases depression and aggression test scores in rats

Abstract: Male rat pups at weaning (21 days of age) were subjected to a diet deficient or adequate in n-3 polyunsaturated fatty acids (n-3 PUFAs) for 15 weeks. Performance on tests of locomotor activity, depression, and aggression was measured in that order during the ensuing 3 weeks, after which brain lipid composition was determined. In the n-3 PUFA-deprived rats, compared with n-3 PUFA-adequate rats, docosahexaenoic acid (22:6n-3) in brain phospholipid was reduced by 36% and docosapentaenoic acid (22:5n-6) was elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
158
3
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(175 citation statements)
references
References 79 publications
(82 reference statements)
12
158
3
2
Order By: Relevance
“…One or a combination of these factors could contribute to increased depression and aggression scores reported in response to n-3 PUFA deprivation in rats. 15,39,[59][60][61][62] As CREB has been implicated in the pathophysiology of depression as well as of bipolar disorder, 33,63,64 n-3 PUFAs' ability to regulate CREB could be related to their effects in these diseases. CREB requires phosphorylation in order to transcribe CREB-regulated genes, including BDNF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One or a combination of these factors could contribute to increased depression and aggression scores reported in response to n-3 PUFA deprivation in rats. 15,39,[59][60][61][62] As CREB has been implicated in the pathophysiology of depression as well as of bipolar disorder, 33,63,64 n-3 PUFAs' ability to regulate CREB could be related to their effects in these diseases. CREB requires phosphorylation in order to transcribe CREB-regulated genes, including BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…The current study indicates that decreased p38 MAPK activity is involved in functional changes observed in n-3 PUFA deprived rats. 15 Fluoxetine also activates the p38 MAPK cascade, 80 suggesting that the depressive symptoms observed in n-3 PUFA deprived rats are related to decreased p38 MAPK activity. Constitutive p38 MAPK activity maintains the expression of rat brain dopamine 81,82 and serotonin transporters 83 and n-3 PUFA deprivation upregulates D1 and D2 receptors 84 and decreases stimulated serotonin release, 85 all of which are believed to be involved in depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If reliable rodent models of bipolar disorder are developed, it would be useful to test if they are associated with increased AA turnover and AA incorporation into brain phospholipids using quantitative autoradiography and/or chemical analysis. In this regard, 15 weeks of nÀ3 polyunsaturated fatty acid deprivation in rats increased their depression and aggression scores 143 and these altered behavioral scores were associated with increased cPLA 2 activity, protein and mRNA as well as increased COX-2 protein and mRNA expression in the frontal cortex. 144 Approaches to developing novel therapeutics for bipolar disorder by targeting the AA cascade Chronic, therapeutically relevant doses of lithium, carbamazepine and valproate decrease the brain concentration of PGE 2 and the turnover of AA but not of DHA in brain phospholipids of the unanesthetized rat, albeit via different mechanisms ( Figure 3 and Table 2).…”
Section: Observations Related To Aa In Bipolar Disorder Patientsmentioning
confidence: 99%
“…Fifteen weeks of n-3 PUFA deprivation in rats also increased test scores of depression and aggression, behaviors that are found in bipolar disorder in humans. 23 The frontal cortex has been implicated in the pathogenesis of bipolar disorder. [24][25][26] In light of this and to better compare our results with previous findings, [27][28][29][30] we examined the expression and activities of enzymes that regulate AA and DHA metabolic cascades in frontal cortex of n-3 PUFA deprived and adequate rats.…”
Section: Introductionmentioning
confidence: 99%